Umbilical Cord Haematoma and Uterine Torsion: Rare Pregnancy Complications at Tu Du Hospital in Vietnam and a Review of Literature - Anh Dinh Bao Vuong; Phuc Nhon Nguyen (European Medical Journal)
Umbilical cord haematoma (UCH) and uterine torsion are extremely rare complications in pregnancy. These abnormalities may present in acute and spontaneous conditions, however, they should not be neglected in clinical practice when monitoring an abnormal fetal heart without other suspects. The authors hereby report a rare case of UCH and uterine torsion as well as a review of the literature. A female, aged 35 years old (gravida 1, para 0), was admitted to the Emergency Department of Tu Du Hospital, Ho Chi Minh City, Vietnam, due to term gestation without complaints. They had an uncomplicated pregnancy, except a large uterine fibroid and cervical pessary which prevented pre-term birth from 28 weeks of gestational age. A very rare complication of UCH was revealed accidentally following emergency caesarean section associated with abnormal fetal heart rate tracing. Asymptomatic uterine torsion was noticed at the same time as this dramatic event. Pre-operative diagnosis of two rare complications was missed; hence, the authors timely delivered the baby based on another modality of management, computerised cardiotocography. In conclusion, UCH along with uterine torsion is difficult to diagnosis due to its rarity; it is usually an incidental finding. Moreover, no available imaging modality could investigate UCH prior to delivery. Surveillance on fetal heart rate monitoring may be helpful in this fatal situation.